Measurement of the t(t)over-bar production cross section in pp collisions at root s=8 TeV in dilepton final states containing one tau lepton - (:unkn) unknown (ELSEVIER, 2014)
The top-quark pair production cross section is measured in final states with one electron or muon and one hadronically decaying tau lepton from the process t (t) over bar -> (l nu(l))(tau nu(tau))b (b) over bar, where l = e, mu. The data sample corresponds to an integrated luminosity of 19.6 fb(-1) collected with the CMS detector in proton-proton collisions at root s = 8 TeV. The measured cross section sigma(t (t) over bar) = 257 +/- 3 (stat) +/- 24 (syst) +/- 7 (lumi) pb, assuming a top-quark mass of 172.5 GeV, is consistent with the standard model prediction. (C) 2014 The Authors. Published by Elsevier B.V.
Keywords: CMS; Physics; Top quark; Tau